An application of fuzzy AHP/DEA methodology for the facility layout design in the presence of both quantitative and qualitative data - Tuzkaya, UR; Ertay, T (WORLD SCIENTIFIC PUBL CO PTE LTD, 2004)
An effective facility layout evaluation procedure necessitates the consideration of qualitative criteria, e.g. flexibility in volume and variety and quality related to the product and production, as well as quantitative criteria such as material handling cost, adjacency score, shape ratio, material handling vehicle utilization, etc. in the decision process. This paper presents a decision-making methodology based on data envelopment analysis (DEA), which uses both quantitative and qualitative criteria, for evaluating Facility Layout Design (FLD). A computer-aided layout-planning tool, VisFactory, is adopted to facilitate the layout alternative design process as well as to collect quantitative data. Fuzzy AHP is then applied to collect qualitative data related to quality and flexibility. DEA methodology is used to solve the layout design problem by simultaneously considering both the quantitative and qualitative data. The purposed integrated procedure is applied to a real data set consisting of twelve FLDs provided of the plastic profile production system.
Keywords: Computer Science